2020
DOI: 10.3389/fneur.2020.01048
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioral and Neural Correlates of Cognitive Training and Transfer Effects in Stroke Patients

Abstract: Stroke lesions are frequently followed by cognitive impairments. Cognitive training is a non-pharmacological intervention that can promote neural compensation mechanisms and strategies to remediate cognitive impairments. The aims of this study were: (1) To investigate the cognitive performance, generalization effects, and neural correlates of semantic organization strategy training (SOST) in patients with chronic left frontoparietal stroke and healthy controls (HC); and (2) to compare the behavioral effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Many cognitive rehabilitation strategies, usually focused on the specific domains that are impaired in each patient, are employed to treat cognitive disorders in stroke patients, principally by neuropsychologists and speech therapists. Some studies have revealed a number of the neural mechanisms involved in the efficacy of these interventions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many cognitive rehabilitation strategies, usually focused on the specific domains that are impaired in each patient, are employed to treat cognitive disorders in stroke patients, principally by neuropsychologists and speech therapists. Some studies have revealed a number of the neural mechanisms involved in the efficacy of these interventions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors thus concluded that it is within this demographic that cognitive training has the most potential to slow cognitive decline in individuals with MCI [2]. Moreover, another review by Miotto et al has shown that individuals with MCI retain a degree of neuroplasticity, indicating that cognitive training can be a feasible treatment avenue for this population [11]. Overall, a plethora of evidence supports that cognitive training has positive effects on individuals with MCI by slowing cognitive decline and reducing the rate of progression to dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os danos desencadeados pelo AVC encontram-se frequentemente os déficits motores e cognitivos (incluindo alterações de humor), estes prejuízos ocorrem em mais de um terço dos pacientes e podem persistir por anos produzindo disfuncionalidades (Einstad et al, 2021;Jonsdottir et al, 2021;Kuan et al, 2022;Miotto et al, 2020;Morishita & Hummel, 2017)O prejuízo cognitivo pós AVC pode inibir o processo de reabilitação física devido a problemas de memória e mau julgamento (anosognosia), além disso resulta em piores desfechos em longo prazo, como nas atividades de vida diária (AVD), reintegração na comunidade e qualidade de vida (Rohde et al, 2019).…”
Section: Introductionunclassified